Evolutionary Relationships of the Triatoma matogrossensis Subcomplex, the Endemic Triatoma in Central-Western Brazil, Based on Mitochondrial DNA Sequences - Gardim, Sueli; Rocha, Claudia S.; Almeida, Carlos E.; Takiya, Daniela M.; Silva, Marco T. A. da; Ambrosio, Daniela L.; Cicarelli, Regina Maria Barretto [UNESP]; Rosa, João Aristeu da [UNESP] (Amer Soc Trop Med & Hygiene, 2013)
The phylogenetic relationships among species of Triatoma matogrossensis subcomplex (T. baratai, T. guazu, T. matogrossensis, T. sordida, T vandae, and T. williami) was addressed by using fragments of cytochrome oxidase I (COI), 16S rDNA (16S), and cytochrome b (Cytb) through Bayesian and parsimony analyses. We did not recover a monophyletic T matogrossensis subcomplex, and their members were found clustered in three strongly supported clades, as follows: i) T. jurbergi + T. matogrossensis + T. vandae + T. garciabesi + T. sordida; ii) with T guasayana as the sister group of clade (i); and iii) T. wilhami + T. guazu, however not closely related to the clade formed by the previously mentioned species. The other two endemic species from Central-Western Brazil, T. baratai and T. costalimai, were not recovered with strong clade support as related to other members of this subcomplex. Results call for a further revision in the classification of the subcomplexes within the genus Triatoma.